PENGARUH PENGGUNAAN METODE TWO STAY TWO STRAY TERHADAP KETERAMPILAN MENULIS KARANGAN TEKS DESKRIPSI SISWA KELAS X SMKN 1 KOTA BUKITTINGGI - Lili Hasmi (Ensiklopedia of Journal, 2019)
This research is based on the problems experienced in learning Indonesian especially in writing deskripsi texts among others as follows: (1). the problem that is often encountered in writing deskripsi text lessons is the lack of variation in the use of learning methods, thus making students less motivated in writing exposition texts. (2). students find it difficult to determine the right diction in expressing an opinion. (3). Lack of facilities and infrastructure supports in the skills of writing deskripsi texts. (4). students are less able to write into a coherent sentence. (5). students are less able to express an opinion of the observed object .. This study aims to (1) know the influence of TSTS learning methods on writing skills texts deskripsi of students of class X SMK Negeri 1 kota Bukittinggi. (2) know pengearuh conventional method of writing skill deskripsi text of students of class X . (3) to know the difference of learning influence using TSTS method and conventional teaching method to writing skill deskripsi text of class X . This is seen in the comparison of tcount with ttable (7.89> 2.021), because tcount is bigger than ttable then Ha (Alternative Hypothesis) is accepted. Thus the result of the improvement between the control class and the experimental class is an increase of 19.12%, it can be said that the learning of Two Stray Two Stay method is better than the conventional learner.